A New Algorithm With Different Modulation Index (Mi) In Cascaded H-Bridge Multilevel Inverters (CHB MLIS) - Omar, Rosli; Sulaiman, Marizan; Abd Halim, Wahidah; Al-Hiealy, Mohammed Rasheed Jubair; Johan, Norsahjatulnizam; Mies, Nizam; Krismadinata, Krismadinata (JATIT & LLS, 2019)
The output waveforms of the multilevel inverters must be maintained smooth and not highly contents of the harmonics.Due to that the research of the multilevel inverters is still relevant to explore. For maintaining sinusoidal of the output waveforms of the multilevel inverters the design of an appropriate controller is crucial, hence the best controllers must be chosen. The suitable and its performance of the controllers will determine whether the output waveforms of the multilevel inverters can reduce the harmonics contains or not. This research aimed to investigate the performance of the Firefly Algorithm (FFA) which is applied to the modified cascaded H-Bridge multilevel inverters (MCHBMLIs) for five levels for harmonics reduction of the MCHBMLIs output waveforms especially for the currents and the voltages with different modulation index (MI). FFA is considered as an easy way which is aims to compute of the switching angle to be optimized for harmonics reduction in the proposed inverters.The concept is based on the Selective Harmonics Elimination (SHE) and the FFA is capable to reduce the lower order harmonics in the output voltages and currents of the waveforms. In order to validate the effectiveness of the proposed algorithm a simulation model has been built up. The parametric model of the simulation to be a benchmark to build up a prototype. Finally the experimental results are a good agreement with the simulation results